2019
DOI: 10.21037/tgh.2019.03.01
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic bariatric therapies for treating obesity: a learning curve for gastroenterologists

Abstract: Obesity represents a growing public health threat. Until recently, surgery was the primary means for treating pharmacotherapy resistant obese patients. However, therapeutic endoscopy has evolved as an effective and safe alternative strategy. Particularly, endoscopic bariatric therapy (EBT) can bridge the gap in patients who do not fit the BMI criteria for surgery and fail conservative or medical therapy. Today there are many tools within the realm of EBT available to endoscopists. While there are no formal gui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 65 publications
0
32
0
Order By: Relevance
“…A few studies have attempted to define learning curves with endoscopic sleeve gastroplasty, a gastricrestrictive procedure commonly performed with endoscopic suturing. [40][41][42] However, threshold numbers to achieve "efficiency" varied greatly from 7 to 38 cases, due to the heterogeneous definitions and variable outcome measures across the studies. These data were based on endoscopists who had extensive previous experience with the endoscopic suturing device.…”
Section: Endoscopic Bariatric Therapiesmentioning
confidence: 99%
“…A few studies have attempted to define learning curves with endoscopic sleeve gastroplasty, a gastricrestrictive procedure commonly performed with endoscopic suturing. [40][41][42] However, threshold numbers to achieve "efficiency" varied greatly from 7 to 38 cases, due to the heterogeneous definitions and variable outcome measures across the studies. These data were based on endoscopists who had extensive previous experience with the endoscopic suturing device.…”
Section: Endoscopic Bariatric Therapiesmentioning
confidence: 99%
“…To address this issue, national organizations such as the American College of Gastroenterology (ACG), AGA, and ASGE are considering the introduction of advanced fellowships in EBT. 61 In addition to education and training, a formal and uniformly approved certification of a theoretical and practical curriculum should be developed for endoscopists or surgeons who wish to perform endoscopic bariatric procedures. For this purpose, the Association for Bariatric Endoscopy (ABE), an ASGE division, has identified three principles to provide quality EBT as follows: (1) a deep knowledge of obese patients' management, (2) the mastery of GI endoscopic skills with procedure-and device-specific competency, and (3) the management of potentially adverse events.…”
Section: Revision Proceduresmentioning
confidence: 99%
“…To address this issue, national organizations such as the American College of Gastroenterology (ACG), AGA, and ASGE are considering the introduction of advanced fellowships in EBT. 61…”
Section: Br Trainingmentioning
confidence: 99%
“…Obesity is a significant public health epidemic with an increasing number of related complications with rising healthcare costs. 1 3 The prevalence of obesity has doubled since the 1980s, with the World Health Organization (WHO) 2014 estimates of 600 million obese adults. 1 Studies have shown that bariatric surgery improves obesity-related complications along with the improved quality of life.…”
Section: Introductionmentioning
confidence: 99%